THE ROLE OF GENDER ON ESL LEARNERS’ PERCEPTION IN ENGLISH LANGUAGE LEARNING: A SYSTEMATIC REVIEW - Partibaraaj Nagasundram; Suyansah Swanto; Megawati Soekarno; Wardatul Akmam Din, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
ESL learners have varying perceptions towards their English language learning experience because no one student is alike with the other. Gender differences is an important aspect of ESL learners’ identity which is frequently overlooked because English curriculums and teaching methods are usually carried out in classrooms with a one-size-fits-all concept, and does not cater to the different needs and learning styles of their students. This study aims to determine whether gender plays a significant role in shaping ESL learners’ perceptions towards English language learning. This study was conducted via the systematic literature review method. A total of ten literatures were chosen for inclusion in this study based on specified criteria and gathered from various online journal databases. Based on the results, it was found that gender does play an important role on ESL learners’ perception due to societal and environment factors that feed into stereotypical gender roles. Also, the inherent biological and psychological differences between males and females can affect ESL learners’ perceptions and attitudes when learning English.